Aufzucht, Spermaproduktion und Befruchtungserfolg bei Ayrshirebullen in der Besamungsstation Salpausselkä - Klautschek, G.; Uusisalmi, U. (Agricultural and Food Science, 1973)
The rearing, feeding and management of A. I. bulls are of importance to their semen production and fertility. Analyses were consequently made of performance testing results, quantity and quality of semen production and insemination results in respect of 44 Ayrshire bulls. Non-return rates were calculated from a total of 57 289 first inseminations. The Ayrshire bulls were reared to the age of one year at the Humppila Performance Testing Station in 1967–69. The bulls were weighed during the experiment at intervals of 30 days. Measurements were taken at the age of 180 days and 365 days. The quantity and quality of semen production of the bulls were measured from the age of 12 months to the age of 24 months. The non-return rates were calculated for at least the first two years of insemination. The number of first inseminations varied from bull to bull between 666 and 3 509. Non-return rates for the bulls varied from 62.3 % to 90.0 % in the first year of insemination and from 58.3 % to 89.2 % in the second. The differences between the bulls were significant. In the study Uusisalmi et al. (1973) found that bulls that had gained well also produced semen well. In the present study by contrast, the results of the performance testing showed a negative correlation with the non-return rate. The non-return rates likewise showed a negative correlation with the measurements taken at the age of 180 days and 365 days. When the bulls were classified as light and heavy, the non-return percentages obtained with the lightweight bulls were found to be significantly higher than those for the heavy bulls. The correlations were calculated between the non-return rates of the bulls on the one hand and the absolute and relative milk and fat yields of their parents on the other, and the correlations were generally found to be negative. However, only the correlation between the non-return rate of the bulls and the fat percentage of the sires was statistically significant (r = –0.45**). The results may be regarded as suggesting that the increasing of production level through breeding might lead to reduced non-return rates. The study shows that the semen production capacity and the NR % of A. I. bulls should be assessed together with the characteristics of milk and meat yield, in order to prevent in due time any unfavourable development in fertility characteristics.